THE REALITY OF KNOWLEDGE MANAGEMENT IN CONTEMPORARY ORGANIZATIONS AND ITS IMPACT ON IMPROVING INSTITUTIONAL PERFORMANCE - Bushra Abbas Shaker (Scholar Express Journals, 2026)
Know-how is an important element to build upon and learn about in today's business world that is full of changes, intense competition, and rapid technological development. The material and financial-based resources are no longer enough to achieve the excellence of an institution, but rather the organizational knowledge is a more significant source in increasing efficiency and improving institutional performance. This study seeks to understand the state of knowledge management in modern organizations, through studying the practices and tools associated with this concept, discovering the extent to which it is adopted in different organizational settings and revealing its contribution in institutions’ performance development covering administrative, financial and operational performance along with services’ quality. The study may also provide some insight into the relationship of KM processes (knowledge creation, preservation, sharing and application) as to how they contribute to improving employee performance, creating new ideas and facilitate decision-making
Keywords: Knowledge management; organizational performance; intellectual capital; organizational innovation